Preparation method, product and application of functional LuPeltier tear-like Janus silicon dioxide particles

The preparation of functional Rupert tear-shaped Janus silica particles by one pot method solved the problem of low functional partitioning and complex preparation process of Janus particles in the prior art, and achieved excellent self-driven interface catalytic performance and fast directional movement.

CN119191306APending Publication Date: 2024-12-27YINGKOU INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411307225.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The functional partitioning degree of existing Janus particles is not high, the preparation process is complex and costly, making it difficult to meet the complex technical requirements across fields.

Method used

A one-pot method is used to prepare functional Rupert tear-shaped Janus silica particles. By adding silane precursor and silane coupling agent to the alcohol-water reaction system, the solid silica rod at one end and the other end are achieved. The combination of hollow silica tails uses hydrogen peroxide as chemical fuel for rapid directional driving.

Benefits of technology

It has achieved the improvement of functional partitioning, simplified preparation process, excellent material performance, self-drive interface catalytic performance, and can achieve rapid directional motion of 12μm/s under the driving of hydrogen peroxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191306A_ABST
    Figure CN119191306A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method, a product and application of functional LuPeltier tear-like Janus silicon dioxide particles, and belongs to the technical field of preparation and application of Janus materials. The preparation method comprises the following steps: dissolving a dispersing agent in an alcohol solution to obtain a continuous phase solution, and then adding water, a catalyst and a structure stabilizer into the continuous phase solution to obtain an alcohol-water reaction system; adding a silane precursor 1 into the alcohol-water reaction system for reaction 1, and then adding a silane precursor 2 and a silane coupling agent into the reaction liquid for reaction 2 to obtain the anisotropic Janus silicon dioxide particle with a hard solid silicon dioxide short rod at one end and a soft hollow silicon dioxide tail at the other end. The two ends of the particle are modified respectively, functional partitioning can be achieved, and the functionalized Janus particle has double groups at the same time, so that the functional Janus particle has interface characteristics and is beneficial to compounding of more functional components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation and application of Janus materials, and in particular to a preparation method, product and application of functional Rupert's tear-shaped Janus silica particles. Background Art

[0002] Anisotropy is the embodiment of directionality and one of the basic properties of the material world. Compared with isotropic materials, anisotropic materials have rich structural characteristics, so they can achieve more complex functions. For many years, researchers have mainly focused on the development of new materials and the study of structural properties in the exploration of anisotropic materials. With the continuous development of science and technology, isotropic materials are increasingly difficult to meet the complex technical requirements in cross-domain work. Therefore, the functional requirements for anisotropic materials are constantly increasing, which has greatly promoted the development and design of anisotropic materials. In fact, the expression of anisotropy in macroscopic manifestations is inseparable from the special properties of microscopic scale components. By simulating the intersection of structure and function found in nature, people can obtain more and more complex materials. These materials are widely used in various fields such as energy collection and drug delivery. In particular, anisotropy at the nanoscale has been proven to significantly improve material performance. As an important branch of anisotropic materials, Janus materials have attracted much attention due to their clear chemical component partitioning and the ability to achieve an effective way to integrate multiple functions. Therefore, they are also widely used in various fields. At present, the research on Janus materials mainly focuses on the micro-nano scale, and its structural design, functional expansion and fine-tuning have been the key areas of concern for researchers for a long time.

[0003] At present, the raw materials for preparing silica micro-nanoparticles are cheap and easy to obtain. Usually, simple silanes such as ethyl orthosilicate and methyl orthosilicate are selected as precursors, and the materials are prepared by hydrolysis-condensation. The usual Janus particle preparation method is relatively complicated and requires multiple reaction steps. Each step of centrifugation and washing will cause certain losses to the product, and the degree of functional zoning needs to be improved. Therefore, it is urgent to develop a preparation process with mild reaction conditions and simple structure. Summary of the invention

[0004] In view of the problems of low functional zoning degree, complicated preparation process and high cost of existing Janus particles, the present invention aims to provide a preparation method, product and application of functional Rupert's tear-shaped Janus silica particles.

[0005] The preparation method provided by the present invention successfully prepares functional Rupert's tear-shaped Janus silica particles with obvious anisotropic partitions, and the asymmetric morphology is highly adjustable. The functional partitioning degree of Janus particles and the simplification of the preparation method achieve better results than the existing technology. The material and its preparation method realize the morphology design under different silanes and reaction conditions, and the functional design under different silane coupling agent modifications and metal effects. One end of the Janus particle is selectively modified with a silane coupling agent to achieve the dual functional characteristics of the particle. Using hydrogen peroxide as a chemical fuel, a fast directional driving property with an average rate of 12 μm / s is achieved. The functional Rupert's tear-shaped Janus silica particles provided by the present invention are an interfacial catalytic material with excellent performance.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention is a method for preparing functional Rupert's tear-shaped Janus silica particles, comprising the following steps:

[0008] Dissolving a dispersant in an alcohol solution to obtain a continuous phase solution, and then adding water, a catalyst and a structural stabilizer to the continuous phase solution to obtain an alcohol-water reaction system;

[0009] The silane precursor 1 is added to the alcohol-water reaction system to carry out reaction 1, and then the silane precursor 2 and the silane coupling agent are added to the reaction solution to carry out reaction 2, so as to obtain the Rupert's tear-shaped Janus silica particles.

[0010] The second technical solution of the present invention is to prepare functional Rupert's tear-shaped Janus silica particles using the above preparation method.

[0011] The third technical solution of the present invention is an application of the above-mentioned functional Rupert's tear-shaped Janus silica particles in the field of self-driven interfacial catalysis.

[0012] The present invention discloses the following technical effects:

[0013] The functional Rupert's tear-shaped Janus silica particles provided by the present invention are obtained by a one-pot method using an improved emulsion interface materialization method, and are composed of a solid silica rod at one end and a hollow silica tail at the other end. The rod length is 100 to 900 nm, and the hollow tail length is 100 to 2000 nm. Both ends can be functionalized and partitioned and composited with metals.

[0014] Compared with the prior art, the preparation method provided by the present invention selects common silanes such as ethyl orthosilicate and methyl orthosilicate as raw materials, and realizes the preparation and regulation of complex structures by a one-pot method. The preparation process is simpler and the conditions are milder. And the self-driving performance is good. Under the drive of hydrogen peroxide, the rapid directional movement of 12 μm / s is achieved in the first 15 seconds. However, the self-driving movement of one-dimensional materials with similar morphology is currently greatly hindered. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 The figures are scanning electron microscope images and transmission electron microscope images of the silica particles in Example 1; wherein (a) and (b) are scanning electron microscope images of silica nanorods at different magnifications, (c), (d), and (e) are scanning electron microscope images of Rupert's tear-shaped Janus silica particles at different magnifications, and (f) is a transmission electron microscope image of Rupert's tear-shaped Janus silica particles.

[0017] Figure 2 FTIR spectrum of Rupert's tear-shaped Janus silica particles in Example 1.

[0018] Figure 3 The scanning electron microscope and energy dispersive spectrometer analysis of the thiol-functionalized Rupert's tear-shaped Janus silica particles in Example 2.

[0019] Figure 4 is the structural formula of 3-mercaptopropyltriethoxysilane in Example 2.

[0020] Figure 5 The scanning electron microscope and energy dispersive spectrometer analysis of the Pt-composite Rupert's tear-shaped Janus silica particles in Example 3, wherein (a) is the micro-region of the solid part, and (b) is the micro-region of the hollow tail.

[0021] Figure 6 The motion trajectories of the Pt-composite Rupert's tear-shaped Janus silica particles in two hydrogen peroxide solutions with different concentrations in the effect verification example, wherein (a) is in a hydrogen peroxide solution with a concentration of 3%, and (b) is in a hydrogen peroxide solution with a concentration of 1%.

[0022] Figure 7This is a statistical diagram of the movement speed of Pt-composite Rupert's tear-shaped Janus silica particles within 15 seconds at different hydrogen peroxide concentrations in the effect verification example. DETAILED DESCRIPTION

[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0024] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0025] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0026] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0027] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0028] The present invention utilizes a solid part and a hollow part to realize Rupert's tear-shaped Janus particles with different hardness at both ends. Solid and hollow structures can be easily prepared from silicon dioxide. Silicon dioxide also has hydroxyl functional groups on its surface that are easy to modify, so this feature can be used to functionalize its surface, and selective modification in specific areas can obtain anisotropic Janus silicon dioxide composite particles with clear functional partitions. Selective modification can make the functional particles anisotropic when composited. If one end of the particle is extremely hydrophilic and the other end is extremely hydrophobic, it can show excellent amphiphilicity and become an excellent interface material, suitable for particle emulsifiers, and can be used to construct a microreactor that can be stable at the oil-water interface.

[0029] By utilizing the selective materialization reaction at the interface of the inverse emulsion, a complex anisotropic particle system can be obtained in one pot. By utilizing the large number of active groups on the silica seed particles, different silane coupling agents and composite materials can be modified, expanding the designability of the structure and function of the Janus particles. The process can be carried out at room temperature and pressure, is easy to operate, and is suitable for promotion.

[0030] Specifically, the present invention provides a method for preparing functional Rupert's tear-shaped Janus silica particles, comprising the following steps:

[0031] Dissolving a dispersant in an alcohol solution to obtain a continuous phase solution, and then adding water, a catalyst and a structural stabilizer to the continuous phase solution to obtain an alcohol-water reaction system;

[0032] The silane precursor 1 is added to the alcohol-water reaction system to carry out reaction 1, and then the silane precursor 2 and the silane coupling agent are added to the reaction solution to carry out reaction 2, so as to obtain the Rupert's tear-shaped Janus silica particles.

[0033] When the silane precursor 1 and the silane precursor 2 are added into the reaction system for reaction, the silane precursor 1 and the silane precursor 2 undergo hydrolysis, condensation and materialization reactions in the reaction system, and finally Rupert's tear-shaped Janus silica particles are obtained.

[0034] In some embodiments of the present invention, the dispersant is polyvinyl pyrrolidone K17, polyvinyl pyrrolidone K30 or polyvinyl pyrrolidone K90, preferably polyvinyl pyrrolidone K30; the catalyst is ammonia water, sodium hydroxide or triethanolamine, preferably ammonia water; the concentration of ammonia water is 25wt%; the structural stabilizer is citric acid, sodium citrate or potassium citrate, preferably sodium citrate; the dosage ratio of the dispersant, catalyst and structural stabilizer is 0.8-1.5g:180-200μL:0.01-0.03mmol, preferably 1g:190μL:0.018mmol.

[0035] In some embodiments of the present invention, the alcohol solution is methanol, ethanol, n-butanol, n-propanol, n-pentanol or n-octanol, preferably n-pentanol; the volume mass ratio of the alcohol solution to the dispersant is 10-15mL:0.8-1.5g, preferably 10mL:1g.

[0036] In some embodiments of the present invention, water is added to the continuous phase solution as a dispersed phase, and the amount of water added is such that the catalyst and the structure stabilizer can be uniformly dispersed in the continuous phase.

[0037] In some embodiments of the present invention, after adding water, catalyst and structure stabilizer to the continuous phase solution, the present invention further comprises the step of fully vortexing the obtained mixed system. The present invention does not specifically limit the vortexing time, and a technical solution familiar to those skilled in the art can be selected.

[0038] In some embodiments of the present invention, the silane precursor 1 and the silane precursor 2 are each independently selected from methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate or 1,2-bis(triethoxysilyl)ethane, and the silane precursor 1 and the silane precursor 2 are different; the silane coupling agent is at least one of n-octyltriethoxysilane, n-hexadecyltrimethoxysilane, n-hexadecyltriethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane.

[0039] In some embodiments of the present invention, the silane precursor 1 is ethyl orthosilicate, the silane precursor 2 is methyl orthosilicate, and the silane coupling agent is 3-mercaptopropyltriethoxysilane.

[0040] In some embodiments of the present invention, the volume mass ratio of the silane precursor 1, the dispersant, the silane precursor 2 and the silane coupling agent is 40-55 μL:0.8-1.5 g:140-160 μL:350-400 μL, preferably 50 μL:1 g:150 μL:400 μL.

[0041] In some embodiments of the present invention, the reaction temperatures of reaction 1 and reaction 2 are both 20-30° C., and the reaction times are both 8-24 h.

[0042] In some embodiments of the present invention, the reaction 1 and the reaction 2 are carried out by static reaction, magnetic stirring reaction or mechanical stirring reaction, preferably static reaction.

[0043] In some embodiments of the present invention, the reaction temperature of reaction 1 and reaction 2 are both 30° C., and the reaction time is both 24 h.

[0044] The present invention sets the above reaction temperature, time and reaction mode for the following reasons:

[0045] The size of dispersed phase emulsion droplets in the inverse emulsion (when the alcohol in the alcohol-water reaction system is n-pentanol, an inverse emulsion system is formed) is affected by temperature and mixing conditions. When the temperature rises, the thermal motion rate of the emulsion droplets increases, and the aggregation of the emulsion droplets under stirring conditions also increases, resulting in the formation of a large emulsion interface, resulting in uneven particle size of the prepared particles, and even the appearance of capsules and vesicles. The reaction time is preferably sufficient for the silane and silane coupling agent small molecules to fully hydrolyze and condense. A too long reaction process will cause the colloidal particles to fully connect into a macroscopic three-dimensional network structure, that is, to form a gel and solidify the system, which is not conducive to the washing and separation of Janus particles.

[0046] In some embodiments of the present invention, after the reaction 2 is completed, a metal salt and a reducing agent are added to the reaction system to perform an in-situ reduction reaction.

[0047] In some embodiments of the present invention, the metal salt is sodium hexachloroplatinate hexahydrate, sodium tetrachloropalladate trihydrate or tetrachloroauric acid tetrahydrate, preferably sodium hexachloroplatinate hexahydrate; the reducing agent is sodium borohydride, potassium borohydride or hydrazine hydrate, preferably potassium borohydride; the amount of the metal element, the reducing agent and the silane coupling agent in the metal salt is 0.0005mmol: 0.5-0.7mg: 350-400μL.

[0048] The present invention adds metal particles Pt, Pd or Au into Janus particles to give the Janus particles catalytic properties, so that the Janus particles accelerate the decomposition of hydrogen peroxide in a hydrogen peroxide solution.

[0049] In some embodiments of the present invention, the temperature of the in-situ reduction reaction is 20-30° C., and the time is 0.5-1.5 h.

[0050] In some embodiments of the present invention, after the in-situ reduction reaction is completed, the step of centrifuging the reaction solution to separate the Janus particles to terminate the reaction is also included. The present invention does not specifically limit the centrifugal speed and time, and a technical solution familiar to those skilled in the art can be selected.

[0051] The present invention also provides a functional Rupert's tear-shaped Janus silica particle prepared by the above-mentioned preparation method. The Janus particle comprises two parts, a solid short rod and a hollow tail, wherein the short rod is 100 to 900 nm long and the hollow tail is 100 to 2000 nm long. The structure can be functionalized and prepared into a composite functional material. The morphology and size of each part of the Rupert's tear-shaped Janus silica particle can be designed according to the reaction conditions. The two ends can be functionalized and partitioned and composited with metals.

[0052] Rupert's tear-shaped Janus silica particles are typical inorganic colloidal particles. Silanol formed by silane hydrolysis forms Si-O-Si bonds by dehydration or dealcoholization. This step is a crucial link in the silane polymerization process, which promotes the stable connection of the silicon core and the gradual expansion of the structure. Finally, the oligomer SiO2 further polymerizes to form a long chain structure, which expands into a three-dimensional Si-O-Si skeleton structure.

[0053] The functional Rupert's tear-shaped Janus silica particles provided by the present invention have dual functional properties, are easy to asymmetric composite, and improve the designability of material functions.

[0054] The present invention also provides the use of the functional Rupert's tear-shaped Janus silica particles in the field of self-driven interface catalysis.

[0055] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0056] The raw materials, reagents and equipment used in the examples can all be obtained through commercial channels.

[0057] Example 1

[0058] Step 1: Dissolve 1.0 g of polyvinylpyrrolidone K30 in 10 mL of n-pentanol, add 190 μL of aqueous ammonia (25 wt%) as a catalyst, 100 μL of sodium citrate aqueous solution (180 mmol / L) as a structural stabilizer, add 250 μL of water as the dispersed phase, vortex mix for 3 min, and let stand for 15 min to form a transparent and uniform inverse emulsion as a reaction system.

[0059] Step 2: Add 50 μL of tetraethyl orthosilicate to the reaction system obtained in step 1 for hydrolysis. The tetraethyl orthosilicate molecules spontaneously transfer to the interface for condensation and materialization reaction. After reacting at 30°C for 10 hours, add 150 μL of methyl orthosilicate and continue to react at 30°C for 24 hours. The reaction system gradually changes from clear and transparent to white turbid. The product is centrifuged and washed to obtain a white powder.

[0060] Figure 1 The scanning electron microscope and transmission electron microscope images of typical Rupert's tear-shaped Janus silica particles are shown. The entire particle consists of a head and a tubular tail. The head is a solid short silica rod, and the tail is a hollow tubular silica. When 250 μL of deionized water and an ammonia concentration of 122 mmol / L are added to the system, solid rod-shaped nanoparticles can be obtained as seeds within 10 hours at 30°C ( Figure 1(a) and (b)), the average lateral diameter of the head is about 347nm. Then, methyl orthosilicate is added and the reaction is continued for 24h to prepare Rupert's tear-shaped Janus silica particles ( Figure 1 (c)-(f)).

[0061] Figure 2 This is the Fourier infrared spectrum of Rupert's tear-shaped Janus silica particles. The wavelengths of the particles are 3502-3305, 1631-1666 and 1160-1045 cm -1 Within the range, vibrations of -OH, CH, and Si-O bonds can be observed. Experimental verification has shown that the hydrolysis of ethyl orthosilicate and methyl orthosilicate will lead to the generation of silanols. These generated silanols further undergo condensation reactions to form Si-O-Si bonds through dehydration or dealcoholization. This step is a crucial link in the silane polymerization process, which promotes the stable connection of the silicon core and the gradual expansion of the structure. Finally, through polymerization reactions, low polymers are further polymerized to form long chain structures, which expand into three-dimensional Si-O-Si skeleton structures.

[0062] Example 2

[0063] Step 1: Dissolve 1 g of polyvinylpyrrolidone K30 in 10 mL of n-pentanol, add 190 μL of aqueous ammonia (25 wt%) as a catalyst, 100 μL of sodium citrate aqueous solution (180 mmol / L) as a structural stabilizer, add 250 μL of water as a dispersed phase, vortex mix for 3 min, and let stand for 15 min to form a transparent and uniform inverse emulsion as a reaction system.

[0064] Step 2: Add 50 μL of tetraethyl orthosilicate to the prepared reaction system for hydrolysis. The tetraethyl orthosilicate molecules spontaneously transfer to the interface for condensation and materialization reaction. After reacting at 30°C for 10 hours, 150 μL of methyl orthosilicate and 400 μL of 3-mercaptopropyltriethoxysilane are added simultaneously and the reaction is continued at 30°C for 24 hours. The reaction system gradually changes from clear and transparent to white turbid. The product is centrifuged and washed to obtain a white powder.

[0065] Figure 3 This is a scanning electron microscope and energy dispersive spectrometer analysis of thiol-functionalized Rupert's tears-shaped Janus silica particles. The addition of 3-mercaptopropyltriethoxysilane causes the solid short rod-like part to be extended and the hollow tail to be shortened, resembling a worm. In addition to silicon and oxygen elements, the S and C elements are more abundant in the cavity part and less abundant in the solid part, with a clear distinction. This is attributed to more thiol groups attached to one side of the cavity, resulting in obvious anisotropy in the group distribution, forming a typical Janus structure. The structural formula of 3-mercaptopropyltriethoxysilane is as follows: Figure 4 .

[0066] Example 3

[0067] Step 1: Dissolve 1 g of polyvinylpyrrolidone K30 in 10 mL of n-pentanol, add 190 μL of aqueous ammonia (25 wt%) as a catalyst, 100 μL of sodium citrate aqueous solution (180 mmol / L) as a structural stabilizer, add 250 μL of water as a dispersed phase, vortex mix for 3 min, and let stand for 15 min to form a transparent and uniform inverse emulsion as a reaction system.

[0068] Step 2: Add 50 μL of tetraethyl orthosilicate to the prepared reaction system for hydrolysis. The tetraethyl orthosilicate molecules spontaneously transfer to the interface for condensation and materialization reaction. After the reaction has been going on for 10 hours, add 150 μL of methyl orthosilicate and 400 μL of 3-mercaptopropyltriethoxysilane at the same time and continue the reaction for 24 hours. The reaction system gradually changes from clear and transparent to white turbid.

[0069] Step 3: Add 300 μL of sodium chloroplatinate aqueous solution (1 mg / mL) to the reaction system obtained in step 2 and react at 30°C for 24 hours, then add 300 μL of potassium borohydride aqueous solution (2 mg / mL) as a reducing agent. After reduction reaction at 30°C for 1 hour, the color of the system deepens, and the product is centrifuged and washed to obtain a light gray powder.

[0070] Figure 5 This is the scanning electron microscope and energy dispersive spectrometer analysis of Pt-compounded Rupert's tear-shaped Janus silica particles. Affected by the change of reaction environment, Janus particles evolve into a short-tailed cocoon structure. The Pt content in the cavity part reaches 1.7wt%, while the solid part is only 0.2wt%. This is because the high content of S atoms of mercapto groups in the cavity reacts with Pt to form a coordination reaction, which has obvious orientation.

[0071] Effect verification example

[0072] Self-driving test: Pt composite Rupert's tear-shaped Janus silica particles were prepared in Example 3. In this part, the self-driving ability of the particles was tested under different concentrations of hydrogen peroxide. 30 μL of the dispersion of the washed Janus / Pt composite nanoparticles (i.e., the Pt composite Rupert's tear-shaped Janus silica particles obtained in Example 3) and 1% and 3% hydrogen peroxide solutions were respectively taken in centrifuge tubes, and the movement of the particles was immediately observed under a fluorescent inverted microscope each time.

[0073] Figure 6The following are the motion trajectories of Pt-composite Rupert's tear-shaped Janus silica particles in two hydrogen peroxide solutions with different concentrations. The motion distance of the particles as micromotors under different conditions within 15 seconds was analyzed. The motion trajectory of the micromotors under the condition of 3% hydrogen peroxide concentration was longer than that under the condition of 1%. This indicates that within a certain range, as the hydrogen peroxide concentration increases, the Pt single substance and the hydrogen peroxide reaction sites are more aggregated, thereby making the self-driving performance of the particles better. It is worth noting that the Pt nanoparticles are concentrated on the hollow side. This asymmetry minimizes the rotational diffusion effect of the micromotors, so that the micromotors can maintain a specific directionality when chemically driven in the solution.

[0074] Figure 7 The figure is a statistical diagram of the movement speed of Pt composite Rupert's tear-shaped Janus silica particles within 15 seconds under different hydrogen peroxide concentrations. In the system without adding hydrogen peroxide solution, only Brownian motion of particles is observed in the field of view. It shows that the Pt composite antenna-shaped Janus silica particles synthesized by the present invention rely on a certain concentration of hydrogen peroxide as fuel to move. By tracking its movement trajectory, several particles are found in the field of view respectively, and the average movement speed in the peroxide solution with a concentration of 1% is measured to be about 6μm / s, and the average movement speed in the hydrogen peroxide solution with a concentration of 3% is about 12μm / s.

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing functional Rupert's tear-shaped Janus silica particles, characterized in that: The following steps are involved: Dissolving a dispersant in an alcohol solution to obtain a continuous phase solution, and then adding water, a catalyst and a structural stabilizer to the continuous phase solution to obtain an alcohol-water reaction system; The silane precursor 1 is added to the alcohol-water reaction system to carry out reaction 1, and then the silane precursor 2 and the silane coupling agent are added to the reaction solution to carry out reaction 2, so as to obtain the Rupert's tear-shaped Janus silica particles.

2. The method for preparing functional Rupert's tear-shaped Janus silica particles according to claim 1, characterized in that: The dispersant is polyvinyl pyrrolidone K17, polyvinyl pyrrolidone K30 or polyvinyl pyrrolidone K90; the catalyst is ammonia water, sodium hydroxide or triethanolamine; the structural stabilizer is citric acid, sodium citrate or potassium citrate; the dosage ratio of the dispersant, the catalyst and the structural stabilizer is 0.8-1.5g:180-200μL:0.01-0.03mmol.

3. The method for preparing functional Rupert's tear-shaped Janus silica particles according to claim 1, characterized in that: The alcohol solution is methanol, ethanol, n-butanol, n-propanol, n-pentanol or n-octanol; the volume mass ratio of the alcohol solution to the dispersant is 10-15 mL:0.8-1.5 g.

4. The method for preparing functional Rupert's tear-shaped Janus silica particles according to claim 1, characterized in that: The silane precursor 1 and the silane precursor 2 are each independently selected from methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate or 1,2-bis(triethoxysilyl)ethane, and the silane precursor 1 and the silane precursor 2 are different; the silane coupling agent is at least one of n-octyltriethoxysilane, n-hexadecyltrimethoxysilane, n-hexadecyltriethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane.

5. The method for preparing functional Rupert's tear-shaped Janus silica particles according to claim 1, characterized in that: The volume mass ratio of the silane precursor 1, the dispersant, the silane precursor 2 and the silane coupling agent is 40-55 μL: 0.8-1.5 g: 140-160 μL: 350-400 μL.

6. The method for preparing functional Rupert's tear-shaped Janus silica particles according to claim 1, characterized in that: The reaction temperature of reaction 1 and reaction 2 are both 20-30° C., and the reaction time is both 8-24 h.

7. The method for preparing functional Rupert's tear-shaped Janus silica particles according to claim 1, characterized in that: After the reaction 2 is completed, a metal salt and a reducing agent are added to the reaction system to perform an in-situ reduction reaction.

8. The method for preparing functional Rupert's tear-shaped Janus silica particles according to claim 7, characterized in that: The metal salt is sodium hexachloroplatinate hexahydrate, sodium tetrachloropalladate trihydrate or tetrachloroauric acid tetrahydrate; the reducing agent is sodium borohydride, potassium borohydride or hydrazine hydrate; the dosage ratio of the metal element to the reducing agent and the silane coupling agent in the metal salt is 0.0005mmol:0.5-0.7mg:350-400μL.

9. Functional Rupert's tear-shaped Janus silica particles prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the functional Rupert's tear-shaped Janus silica particles according to claim 9 in the field of self-driven interfacial catalysis.